Pengaruh Pandemi COVID-19 Terhadap Motivasi Perilaku dan Metode Online Bagi Mahasiswa FK Undana - Sagita, Sidarta; E. Dedy , Maria Agnes; Artawan, I Made (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Knowledge and attitudes about COVID-19 prevention behavior are very important, especially for health workers themselves, because currently there are health workers who have been confirmed positive for COVID-19. This causes several negative impacts that cause a lot of losses not only for the health workers but for families and students. Research on the effect of the COVID-19 pandemic on behavioral motivation and online methods for students has never been done, especially in East Nusa Tenggara (NTT), especially at Undana Medical Faculty. FK Undana is a public lecturer faculty in NTT. Therefore, researchers are interested in conducting research on "The Effect of the COVID-19 Pandemic on Behavioral Motivation and Online Methods for UNDANA Medical Faculty Students". To increase knowledge about research in general (theoretical) and increase knowledge about COVID-19 in relation to looking at the effect of the COVID-19 pandemic on behavioral motivation and online methods for students. The type of research conducted is quantitative and qualitative research using analytical research design and cross sectional design. This research design is used to examine qualitatively in the interview results. The implementation of the online learning system is still not optimal, with the absence of a learning system study report, a learning system feedback report. The supporting factor in the online learning system is that all lecturers and students understand technology and are accustomed to using the internet. An internet service system that already supports teaching and learning activities. The obstacle factor in the online learning system is that the work of lecturers becomes an obstacle to the teaching and learning process considering that their busyness has increased due to the COVID-19 pandemic, especially prioritizing the service of COVID-19 patients. Students are not ready for a sudden change from an offline learning system to an online learning system.